Can the Current Youth Agricultural Groups be Sustainable? Experiences from Mid-Western Uganda - Loga, Dorcas Elizabeth; Kibwika, Paul; Kyazze, Florence Birungi (Cogent Social Sciences, 2022)
As one of the most youthful populations in the world, with close to 80% of its population under the age of 30, Uganda is grappling with initiatives for engaging youth in productive sectors of the economy. Agriculture is considered the most immediate means of catalyzing economic growth and employment for the youth. The Self-Help Groups (SHGs) Model is preferred by both government and non-government agencies to organize youth to engage in agriculture because it takes into account the critical socio-economic elements. The challenge is how to ensure the sustainability of the SHGs for the progressive transformation of the youth. This article assesses the likelihood forof the sustainability of youth groups engaged in agricultural enterprises, based on the parameters of group sustainability specified by the Producer Organization Sustainability Assessment Model. The study employed a quantitative design using a cross-sectional survey conducted between Government and Non-Governmeagency agenciesagencies supported Self Help Groups. In the study, Non-Government Supported groups were more likely to be sustainable than the Government supported groups. The main contributors to sustainability among the Non-Government supported groups were access to production resources, financial health, and member loyalty, while the main contributors for the Government supported groups were leadership, financial health, and member loyalty.
Keywords: Agriculture; Self-help groups; Youth; Sustainability